Development of a SNaPshot® Multiplex system for the typing of single nucleotide polymorphisms (SNPs) involved in the adaptive response to high altitude hypoxia. (December 2017) - Burgos, G.; Ruano, M.; Badin, M.; Camargo, M.; Tejera, E.; Paz-Y-Miño, C.
Abstract: HIF2-α is the leading gene involved in adaptive response to hypoxia. The codification of this gene regulates the expression of more than 100 genes. SNPs in this gene, affecting the protein HIF2-α, have been linked to the regulation of several tissues proliferation; in multiple diseases and even oncogenic processes. For this reason, the major aim of the study was to develop the first genotyping protocol using SNaPshot ® system in Ecuador. To fulfil the objectives of the present work, a SNaPshot ® -based system was designed to typify seven SNPs. In this manner, commercial control DNAs were used, based on which the conditions of PCR and SNaPshot ® Multiplex were adjusted, finally, the results were validated using Gold Standard method. It was concluded that SNaPshot ® Multiplex system has the same sensitivity and specificity as the Gold Standard, but it is extremely economical, fast, and feasible to implement in developing countries.